Organ Damage due to Elevation of Blood Pressure on NaCl-induced - Hotimah Masdan Salim; Ilham Putra Alam; Widya Dio Kharisma (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2020)
Introduction: High salt diet is known to induce or aggravate hypertension in hypertensive rats and humans. The elevation of blood pressure by NaCl-induced promotes cardiac hypertrophy, the impairment of left ventricular relaxation, endothelial dysfunction, and kidney injury. This study aimed to examine whether NaCl-induced caused increase blood pressure and weight of organs. Methods: Eight weeks old male Mus musculus were divided to two groups, one group was given NaCl 8% by intraperitoneal injection for 8 hours.Results: Blood pressure was measured previously, in this study systolic and diastolic blood pressure increased significantly (p < 0.05). The increasing of blood pressure was followed by significant increase in organ weight, such as heart and kidney (p < 0.05). Conclusion: This result suggested that NaCl-induced caused hypertension and increased organs weight that may cause early process of damages in organs.